Technical Analysis of Influence of Special Treatment on Water Ballast Treatment by using Active Carbon on Vessel and Environment - Aguk Zuhdi Muhammad Fathallah; Fachrul Hidayat Husein (International Journal of Marine Engineering Innovation and Research, 2016)
Ballast water exchange is made by a vessel from one port to another port can cause a problem. The ballast water exchange can be harmful microorganisms that shifts has been be a predator for the ecosystem of the intended recipients. To prevent this, IMO issued several rules regarding the disposal of water ballast, ballast water i.e. issued a ship must be in clean condition or there should be a treatment first before being dumped. Various alternative treatments ever used to be able to satisfy this rule. In this final task, developed one of the alternative treatment with using chemicals activated carbon with the object of study of ship cruise route with SINAR SUMBA Singapore – Surabaya and time planning is designed for 12 hours. The selection of the method of test samples conducted in the laboratories chosen to know the applications the use of activated carbon to water ballasts of Surabaya and Singapore is in compliance with the specified standards. Then the next design planning systems or designs are suitable for use on the ship. From the results of the study shoitd that by using activated carbon- filtration, activated carbon the water turned out to be able to reduce the number of microorganisms such as E. Coli, Vibrio Cholerae, and Intestinal Enterococci in accordance with the IMO standards. Based on the results of the laboratory activated carbon filter design then the water ballast can be realized.